Atmospheric‐Pressure Plasma Deposited Epoxy‐Rich Thin Films as Platforms for Biomolecule Immobilization—Application for Anti‐Biofouling and Xenobiotic‐Degrading Surfaces. Issue 11 (15th May 2015) - Camporeale, Giuseppe; Moreno‐Couranjou, Maryline; Bonot, Sébastien; Mauchauffé, Rodolphe; Boscher, Nicolas D.; Bebrone, Carine; Van de Weerdt, Cécile; Cauchie, Henry‐Michel; Favia, Pietro; Choquet, Patrick
Abstract : In this work, an atmospheric‐pressure dielectric barrier discharge process is exploited for the fast deposition of adherent epoxy‐rich layers acting as a versatile platform for the efficient one‐step biomolecule immobilization in mild aqueous conditions. Particular attention is given to the influence of the plasma process parameters on the chemical and morphological properties of the deposited layers and on their subsequent exploitation for chemical interfacial reactions. As a proof‐of‐concept, two enzymes with drastically different biological properties, namely dispersin B and a laccase, are immobilized onto functionalized metallic surfaces. The pH of the enzyme solution appears as a key parameter to control the amount of immobilized enzyme on the plasma functionalized surfaces, thus leading to bioactive surfaces with improved stability and activity. Abstract : An atmospheric‐pressure method has been developed to efficiently immobilize enzymes onto solid surfaces based on the AP‐DBD deposition of epoxy‐rich layers and its subsequent interfacial one‐step reaction with biomolecules in mild aqueous conditions. The influence of the process parameters on the layer properties as well as the importance of the pH of the solution containing biomolecules on the biological material performances are reported and discussed.